Sterile Inflammation-Do innate lymphoid cell subsets play a role? - Russell, Shane E.; Walsh, Patrick T. (Frontiers in Immunology, 2012)
The recent identification of several novel innate lymphoid cell subsets (iLCs) has increased our understanding of the mechanisms which link the innate and adaptive immune systems. While the contribution of these subsets towards the pathogenesis of human disease remains largely to be determined, it seems likely that they will play a particularly important role in sterile inflammatory settings where the innate response is seen as a critical mediator of inflammation. Several recent studies have highlighted the role of endogenous damage associated molecular patterns such as IL-33, IL-1 and IL-1 in promoting lymphoid cell responses. This review discusses the influence of such endogenous danger signals on novel iLCs such as Lymphoid Tissue-inducer (LTi) cells, innate type 2 helper cells and  T cells and explores how these responses may contribute to the development of an inflammatory response in a sterile setting.